El rasgo [±] animado y las explicaciones funcionales: dos casos de morfosintaxis diacrónica. - Ibáñez Moreno, Ana; Martín Arista, Javier (Estudios Ingleses de la Universidad Complutense, 2001)
This journal article contributes to the notion of functional explanation in diachrony by discussing two independent morphosyntactic evolutions that took place in Early English, namely the rise of the syntactic possessive postmodifier and the replacement of grammatical gender with natural gender. At the theoretical level the role of competing functional principles which account for opposite evolutionary forces is explored, particularly paradigmatic economy and syntagmatic cross-domain harmomy vs. asymmetry in language coding and processing. The conclusion is drawn that the feature [± animate] motivates and restricts paradigm economy and crossdomain harmony, in such a way that the functional explanation of the phenomena under scrutiny constitutes a compromise solution between the morphosyntactic tendency to the maximization of structure and the semantic tendency to the minimization of meaning. 1.